Percutaneous transluminal angioplasty (PTA): START OF A STUDY AND OUTLOOK - Tiscornia, Eduardo; Salice, Mario; Otero, Ana M.; Lagos, Graciela; Balboa, Oscar; Lucinschi, Alicia; Delgado, Fernando; Matteucci, Pablo; Matteucci, Pablo; Cotic, Graciela; Ricciardi, Norma; Gateño, Nisso; et al. (Cirugía del Uruguay, 1982)
Percutaneous transluminal anioplasty (PTA) makes it possible to dilate a stricture or perform vascular disobstruction by means of catheterism. This technique, introduced by Dotter in 1964, has experienced a siniicant dissemination throughou t the world as a cosquence of the uilization of Grüntzig's catheter. Angioplasies have been performed in pracically ali vascular territories, but their indications and long-term resul s ave not as yet been totally deined. However the method has been accepted and the good results obtined have been confirmed, while surgery is either unable to effect revascularizations or, when it is, such procedures entail considerable risk to the patient. We hope that this first successful case of PTA treated in our country will only constitue the beinning of a long-term study for the purpose of evaluating the possibilíties offered by this therapeuic method.